2022
DOI: 10.3390/s22062348
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Medical IoT-Enabled Automated Microscopic Image Diagnosis of Acute Blood Cancers

Abstract: Blood cancer, or leukemia, has a negative impact on the blood and/or bone marrow of children and adults. Acute lymphocytic leukemia (ALL) and acute myeloid leukemia (AML) are two sub-types of acute leukemia. The Internet of Medical Things (IoMT) and artificial intelligence have allowed for the development of advanced technologies to assist in recently introduced medical procedures. Hence, in this paper, we propose a new intelligent IoMT framework for the automated classification of acute leukemias using micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…The authors in [ 15 ] designed a new model based on an intelligent IoMT framework for classifying acute leukemia using microscopic images. The model includes three main steps: collect samples, push to a cloud server, and identify as either leukemia or healthy in cloud server.…”
Section: Methodsmentioning
confidence: 99%
“…The authors in [ 15 ] designed a new model based on an intelligent IoMT framework for classifying acute leukemia using microscopic images. The model includes three main steps: collect samples, push to a cloud server, and identify as either leukemia or healthy in cloud server.…”
Section: Methodsmentioning
confidence: 99%
“…A performance comparison of diagnosis in pediatric hematological malignancies using AI strategies is shown in Table 1. The results of cluster and discriminant analyses for various types of pediatric acute leukemia revealed that a combination of DL analysis and microscopic blood images facilitated the classification of acute leukemia and outperformed expert hematologists with an accuracy of more than 98% [20,21]. The utility of AI in the automatic analysis of microscopy images represented diagnostic accuracy of around 95% in acute promyelocytic leukemia [22], acute lymphoblastic leukemia (ALL) [23,24], and leukemic B-lymphoblast [25], which was optimized by a hybrid model using a genetic algorithm and a residual CNN reaching an accuracy of 98.46% [26].…”
Section: Non-solid Tumor Diagnosismentioning
confidence: 99%
“…The research of Karar et al (2022) proposed an intelligent framework for classifying acute leukemias using blood microscopy images. Former blood samples were collected using digital devices without microscopy and sent to a cloud server.…”
Section: Related Workmentioning
confidence: 99%